COVID-19 mRNA vaccine and antibody response in lactating women - Charepe, Nadia (2021)
Funding Information: We thank Florian Krammer (Icahn School of Medicine at Mount Sinai, New York, USA) for kindly providing SARS-CoV-2 spike expression plasmids and Paula Alves, Pedro Cruz and Rute Castro from IBET for protein production and the support. Funding Information: This work was supported by Gilead Génese (PGG/009/2017) and the European Society for Clinical Microbiology and Infectious Diseases (ESCMID) to HS. HS and JG is supported by FCT through CEECIND/01049/2020 and PD/BD/128343/2017, respectively. ELISA assay was developed in the context of a Serology4COVID consortium, in which Instituto de Biologia Experimental e Tecnológica (IBET) produced and purified the Spike protein. The present publication was funded by Fundação Ciência e Tecnologia, IP national support through CHRC (UIDP/04923/2020). Publisher Copyright: © 2021, The Author(s).